2019
DOI: 10.1016/j.aap.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Traverses, delays and fatalities at railway level crossings in Great Britain

Abstract: This paper investigates relationships between traverses, delays and fatalities to road users at railway level crossings in Great Britain. A 'traverse' means a passage across a level crossing by a road user, who may be a pedestrian, cyclist, or occupant of a road vehicle. The paper finds that the road users with the highest fatality rate per traverse are pedestrians at passive crossings. Their rate is about three orders of magnitude higher than that of users with the lowest risk, who are road vehicle occupants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Most accidents at railway intersections involved pedestrians, and some estimates reached 75% of the total number of accidents. In addition, the mortality rate for pedestrians is higher than among car occupants, especially at passive LCs [16]. The lowest fatality rate per traveller have the road vehicle occupants on railway-controlled LCs.…”
Section: Level Crossing Accidents and Types Of Users Involvedmentioning
confidence: 97%
See 1 more Smart Citation
“…Most accidents at railway intersections involved pedestrians, and some estimates reached 75% of the total number of accidents. In addition, the mortality rate for pedestrians is higher than among car occupants, especially at passive LCs [16]. The lowest fatality rate per traveller have the road vehicle occupants on railway-controlled LCs.…”
Section: Level Crossing Accidents and Types Of Users Involvedmentioning
confidence: 97%
“…The lowest fatality rate per traveller have the road vehicle occupants on railway-controlled LCs. The railway-controlled LCs are safer than active LCs, but railway-controlled LCs caused the greater delays on users [16]. The replacement of railway-controlled LC by active LC will give monetary savings from reduction of traffic delays which will outweigh the losses from the increased casualties.…”
Section: Level Crossing Accidents and Types Of Users Involvedmentioning
confidence: 99%
“…The study was intended to determine potential routes allowing for these delays to be reduced, while the paper also provides conclusions concerning different types of crossings in the United Kingdom and how their operations may be associated with the traffic delays. Paper [6] considers the choice between automatic and railway-controlled crossings on public roads in Great Britain. It is found that the valuation of the reduced delays from adopting automatic crossings typically outweighs the valuation of the losses from the increased casualties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A brief overview of the data is given in Table 1. 8 To improve the risk of near misses and fatalities different solutions are proposed and implemented at Level Crossings. In general, the ORR suggests that safe design, management and operation can significantly improve the user's behaviour, which in effect will reduce the number of accidents and fatalities.…”
Section: Introductionmentioning
confidence: 99%